China Small and Medium Towns Overview - World Bank (Washington, DC, 2013)
Gross Domestic Product (GDP) growth rate substantially exceeded China's population growth, which averaged 1.4 percent annually between 1978 and 2009, and real GDP per capita accordingly grew at 8.6 percent annually during this period. China's urban population resides primarily in city districts (shiqu) and town districts (zhenqu), which constitute the urban core of larger administrative units called cities (shi) and respectively towns (zhen). Cities and towns in China are expansive regions, with administrative territories much larger than in the rest of the world (Chan 2007). Cities are conceptually equivalent to counties in the U.S. and thus the whole of China's territory is basically covered by 287 prefecture and provincial level municipalities, which within their area include 654 city districts - the cities proper in the conventional sense of this word - and 19,322 towns. Each town in turn includes a town district - an urban core that occupies a fraction of the town's area but accounts for most of the town's urban population. While cities and towns as a whole overlap in their administrative boundaries, with multiple towns nested within each city, city districts and town districts are disjoint structures, being urban embryos within the administrative boundaries of territorially larger cities and towns. The main purpose of this study is to examine the development and features of town districts (zhenqu) - the urbanized core of China's towns.